1995
DOI: 10.1164/ajrccm.152.6.8520784
|View full text |Cite
|
Sign up to set email alerts
|

Alpha 1-antitrypsin-deficient variant Siiyama (Ser53[TCC] to Phe53[TTC]) is prevalent in Japan. Status of alpha 1-antitrypsin deficiency in Japan.

Abstract: In contrast to the fact that alpha 1-antitrypsin (alpha 1-AT) deficiency is one of the most common hereditary disorders of Caucasians, deficient variants among Orientals have been recognized to be extremely rare. Only 12 cases of alpha 1-AT deficiency have been reported in Japan, including five cases in which the genetic defects have already been elucidated: Mnichinan (delta Phe52[TTC] and Gly148[GGG]-->Arg148[AGG]), two unrelated cases of Siiyama (Ser53[TCC]-->Phe53[TTC]), a heterozygote of Mmalton (delta Phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
1
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 19 publications
1
41
1
2
Order By: Relevance
“…These data suggest that rare variants may be more common in areas where the main deficient variants (e.g. PI*Z) are less prevalent [Stolk et al 2006], such as Japan, where the most common variant is deficient PI*Siiyama (Ser53Phe), present in most α1-AT-deficient patients [Seyama et al 1995]. The low prevalence of rare variants recently reported in Ireland (0.7%), where the PI*S and PI*Z major AAT variants showed frequencies of 0.05 and 0.02, respectively [Carroll et al 2011], similar to the highest found in European countries, seems to reinforce this hypothesis of an inverse relationship between the more frequent PI*S/ PI*Z variants and rare AAT variants.…”
Section: Discussionmentioning
confidence: 93%
“…These data suggest that rare variants may be more common in areas where the main deficient variants (e.g. PI*Z) are less prevalent [Stolk et al 2006], such as Japan, where the most common variant is deficient PI*Siiyama (Ser53Phe), present in most α1-AT-deficient patients [Seyama et al 1995]. The low prevalence of rare variants recently reported in Ireland (0.7%), where the PI*S and PI*Z major AAT variants showed frequencies of 0.05 and 0.02, respectively [Carroll et al 2011], similar to the highest found in European countries, seems to reinforce this hypothesis of an inverse relationship between the more frequent PI*S/ PI*Z variants and rare AAT variants.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, the expression of liver disease varies widely, from jaundice only at birth, through to cirrhosis, perhaps because of other genetic influences on this aspect of the clinical phenotype [26]. Polymerisation of AAT in this way also underlies the PiMmalton (52Phe deleted) [27] and Siiyama (Ser53Phe) [28,29,30] forms of AATD, that are common in Sardinia and Japan, respectively. A slower rate of polymer formation occurs with the PiS allele (Glu264Val), because the structural change in β-sheet A is not as radical [31, 32], resulting in a milder serum deficiency but little evidence of clinical disease.…”
Section: The Genetics Of Aatdmentioning
confidence: 99%
“…The Siiyama allele is the most common cause of AATD in Japan (Seyama et al 1995), while the Mmalton variant (also known as Mcagliari and Mnichinan) is the most commonly found allele in Sardinia ).…”
Section: Wwwintechopencommentioning
confidence: 99%